Boundary behavior of the squeezing function near a global extreme point. Issue 3 (4th March 2023) - Van Thu, Ninh; Son, Nguyen Thi Kim; Van Tiep, Chu
Abstract : In this paper, we prove that the general ellipsoid D P is holomorphically homogeneous regular provided that it is a WB -domain. Then, the uniform lower bound for the squeezing function near a ( P, r ) -extreme point is also given.